RIDING THERAPY AND ITS CONTRIBUTIONS TO THE DEVELOPMENT OF PERSONS WITH AUTISM - Aparecida Menegon, Michele (Health and Society, 2024)
Autism is a neurodevelopmental disorder, which is present in different classes and ethnicities. Its main characteristics are impairment of language, interaction, socialization, in addition to presenting psychomotor difficulties. This person needs several therapies for their development, and one of them is equine therapy, which shows great results.